Rolandic Cortex Morphology: Magnetic Resonance Imaging-Based Three-Dimensional Cerebral Reconstruction Study and Intraoperative Usefulness - Bunyaratavej, Krishnapundha; Wangsawatwong, Piyanat (Asian Journal of Neurosurgery, 2022)
Background During brain surgery, the neurosurgeon must be able to identify and avoid injury to the Rolandic cortex. However, when only a small part of the cortex is exposed, it may be difficult to identify the Rolandic cortex with certainty. Despite various advanced methods to identify it, visual recognition remains an important backup for neurosurgeons. The aim of the study was to find any specific morphology pattern that may help to identify the Rolandic cortex intraoperatively.Materials and Methods Magnetic resonance imaging of the brain from patients with various conditions was used to create the three-dimensional cerebral reconstruction images. A total of 216 patients with 371 intact hemispheres were included. Each image was inspected to note the morphology of the Rolandic cortex and the suprasylvian cortex. Additionally, other two evaluators exclusively inspected the morphology of the suprasylvian cortex. Their observation results were compared to find the agreements.Results Several distinctive morphology patterns have been identified at the Rolandic cortex and the suprasylvian cortex including a genu, or a knob at the upper precentral gyrus, an angulation of the lower postcentral gyrus, a strip for pars opercularis, a rectangle for the lower precentral gyrus, and a triangle for the lower postcentral gyrus. Combined total and partial agreement of the suprasylvian cortex morphology pattern ranged from 60.4 to 85.2%.Conclusion The authors have demonstrated the distinctive morphology of the Rolandic cortex and the suprasylvian cortex. This information can provide visual guidance to identify the Rolandic cortex particularly during surgery with limited exposure.
Keywords: cerebral cortex; morphology; Rolandic cortex; suprasylvian cortex; three-dimensional reconstruction